Local and Remote Influences on the Heat Content of Southern Ocean Mode Water Formation Regions. Issue 4 (28th April 2021) - Boland, Emma J. D.; Jones, Daniel C.; Meijers, Andrew J. S.; Forget, Gael; Josey, Simon A.
Abstract: The Southern Ocean (SO) is a crucial region for the global ocean uptake of heat and carbon. There are large uncertainties in the observations of fluxes of heat and carbon between the atmosphere and the ocean mixed layer, which lead to large uncertainties in the amount entering into the global overturning circulation. In order to better understand where and when fluxes of heat and momentum have the largest impact on near‐surface heat content, we use an adjoint model to calculate the linear sensitivities of heat content in SO mode water formation regions (MWFRs) to surface fluxes. We find that the heat content of these regions is, in all three basins, most sensitive to same‐winter, local heat fluxes, and to local and remote wind one to eight years (the maximum lead‐time of our simulations) previously. This is supported by sensitivities to potential temperature changes, which reveal the sources of the MWFRs as well as dynamic links with boundary current regions and the Antarctic Circumpolar Current. We use the adjoint sensitivity fields to design a set of targeted perturbation experiments, allowing us to examine the linear and non‐linear responses of the heat content to changes in surface forcing. In these targeted experiments, the heat content is sensitive to both temperature changes and mixed layer volume changes in roughly equal magnitude. Plain Language Summary: The Southern Ocean (SO) is of crucial importance to the global ocean's uptake of carbon and heat. However, due to difficulties in making observations in such a remote and hostile environment, we currently don't know accurately how much heat and carbon enters the SO from the atmosphere. Heat from the SO can get locked away for hundreds to thousands of years in the world's deep oceans, entering through a few key regions. We use a computer model to assess how the heat, fresh water, and wind energy entering through the surface of the SO affects the heat of these key regions. We find that these regions are very sensitive to heat coming in through the surface directly over them, and that winds across a wider area of the SO can affect the heat stored for several years. If we want to estimate the heat stored in these regions more accurately, this information can be used to help us decide where and when it is important to measure the winds and heat entering the ocean better. Key Points: We perform a comprehensive sensitivity study of the heat distribution in mode water formation regions Sensitivities are highest to local same‐winter heat flux changes, and both local and remote wind stress changes up to at least 8 years past High sensitivity regions reveal kinematic links with source waters and dynamic links with boundary current regions